What we must do – An exotic invasive species in paradise - Anderson Eduardo Silva de Oliveira; Marcelo Semeraro Medeiros (Biotemas)
The soft coral Chromonephthea brazilensis was fi rst recorded at Arraial do  Cabo, on the southeastern Brazilian coast. Following studies showed that the presence of C. braziliensis may be a real threat to regional biodiversity, especially to endemic coral species. This study provides a new record of this exotic invasive species in the region. Taking into account the environmental damage caused by this species, its known distribution and dispersal potential, the study presents recommendations for the eradication and monitoring of C. braziliensis in the region, before its  control becomes unfeasible.